A rice protein hydrolase from Serratia marcescens and its specificity in preparation of oligopeptide‐enriched rice protein hydrolysates. Issue 2 (21st May 2022) - Yan, Zheng‐Fei; Zhou, Jian‐Qiao; Yuan, Shuai; Tang, Cheng‐Ye; Wu, Jing
Abstract: A secreted 50‐kDa metalloprotease from Serratia marcescens D15 was identified as rice protein hydrolase (SeMPase), which reached the highest proteolytic activity (477.3 U/ml) in basal medium with 1.5% rice protein (RP) at 35°C and 150 rpm for 48 h. SeMPase exhibited a highest catalytic number for RP (275.8 min −1, K cat ), which contained a highly conserved Zn 2+ ‐binding (HEIGH) domain, Met‐turn (SLMSY), and Ca 2+ binding domain (GGAGND). RP hydrolysates that prepared by SeMPase showed the highest content of oligopeptides at 72.3%, compared to 64.1% from neutrase, 63.0% from alcalase, 50.2% from trypsin, 47.1% from flavourzyme, and 2.41% from pepsin. Our results showed that cleavage sites of SeMPase exposed in RP are more than those of other proteases because both SeMPase cleavage sites and the amino acid composition of RP are rich in Leu, Val, Phe, Glu, and Ala. SeMPase has significant specificity for the preparation of oligopeptide‐enriched RP hydrolysates, which provides a new and highly valued option for industrial preparation of oligopeptide‐enriched protein hydrolysates. Abstract : Rice protein significantly increased the production of Serratia marcescens SeMPase. SeMPase could specifically prepare oligopeptide‐enriched rice protein hydrolysates. The 72.3% of oligopeptide content is highest in preparation rice protein hydrolysates.